Analysis of Factors Affecting the Income of Rice Paddy Farmers in Rural Farming Communities - Jamiludin, Jamiludin; Paembonan, Laendatu; Parinding, Kalvin; Jaya, Andi Herman; Paskual, Meity Ferdiana (Transpublika Publisher, 2025)
This research examines how various factors including farm size, years of agricultural experience, and expenses for seeds, fertilizers, pesticides, and labor impact the earnings of rice cultivators in Nambaru Village, located in South Parigi District, Parigi Moutong Regency. The study employs a quantitative descriptive methodology and was carried out between February and March 2025, gathering data from 60 participants in Nambaru Village. The investigation utilized both primary and secondary data sources. Primary information was collected through direct observation and interviews using questionnaires, while secondary data came from governmental agencies and academic sources, including the Central Statistics Agency (BPS), Department of Food Crops, and Agricultural Extension Services. The analytical approach employed multiple linear regression techniques. Findings reveal that rice farmers in Nambaru Village earn an average of Rp 24,661,676 per hectare during a standard growing season, achieving an efficiency ratio of 3.03 based on Revenue-to-Cost (R/C) analysis. The study demonstrates that when considered together, all six factors namely farm size (X1), agricultural experience (X2), seed expenses (X3), fertilizer costs (X4), pesticide expenditures (X5), and labor costs (X6) collectively show a positive and statistically significant relationship with farmers' income (Y). When examining individual factors, farm size (X1) demonstrates both positive and significant influence on income. Agricultural experience (X2), fertilizer expenses (X4), and pesticide costs (X5) show positive correlations but lack statistical significance. Conversely, seed costs (X3) exhibit a negative and significant relationship with income, while labor expenses (X6) show a negative but insignificant effect on rice farmers' earnings in the study area.